Polymorphism of growth hormone 1 gene in co and Bach Thao breed goats: Is the recessive homozygous BB genotype lethal? - Dang, Minh Lam; Le, Quang; Nguyen, Van Hop; Bui, Anh Phu Nam (Vietnam Journal of Biotechnology, 2024)
Goat is one of the most popular species in Vietnamese animal husbandry. However, phenotypic selection in goats is still popular in breeding programs. Thanks to the introduction of marker-assisted selection, genetics is currently playing a vital role in choosing the elite animals for breeding. One of the molecular markers that has been widely applied in animal husbandry is the GH1 gene (growth hormone 1), which encodes for the GH protein. GH has been known for its essential role in the growth and development of animals. In goats, GH1 polymorphism is significantly associated with performance traits. In this study, we aim to investigate the GH1 frequency in two indigenous goat breeds in Vietnam: the Co and Bach Thao breeds. Our results showed that there were only two genotypes AA and AB detected in Co and Bach Thao breeds. In the Co goat breed, the frequency of AA and AB genotypes was 0.1 and 0.9, respectively. The frequency of A and B alleles was 0.55 and 0.45, respectively. In the Bach Thao goat breed, the frequency of AA and AB genotypes was 0.16 and 0.84, respectively. The frequency of the A and B alleles was 0.58 and 0.42, respectively. Chi-square values obtained from the Co and Bach Thao goat breeds revealed that there was a significant deviation from the Hardy-Weinberg Equilibrium in both breeds (33.47 and 32.31, respectively, with P<0.001). The lack of BB genotype led us to hypothesize that there was overdominance in three genotypes of GH1 and that the BB homozygous genotype is lethal. We suggested that phenotypic observation would be recommended to measure the superiority of the AB genotype goat compared to the AA genotype goats. The results from this study would be beneficial to goat breeders in improving the goat breeding program in Vietnam.